The Depiction of Human Nature through Allegory: An Analysis of Golding's Lord of the Flies - Ghimire, Surendra Prasad (Indonesian Journal of English Language Studies (IJELS), 2023)
This article critically analyzes Golding's Lord of the Flies to investigate how human nature was allegorically depicted by constructing an almost parallel fictional world to his contemporary time. In this paper, I argued that Golding allegorically exhibited the basic human nature of his contemporary time by experimenting with the schoolboys on the Pacific Ocean, which unveiled the brutal and uncivilized nature of schoolboys, and that such activities as depicted in the novel resembled the brutal and savage nature of the men of his time. The methodology I employed in this study was a close analysis of the primary text to examine how Golding used allegory to uncover the basic nature of human beings, and I analyzed secondary resources related to the study to support my arguments. The analysis identified that Golding depicted savagery and animalistic human nature through allegory, which questioned the traditional understanding of human nature as civilized and moral, and his experience of involving himself in the war and working as a school teacher helped him in reflecting such brutal and uncivilized events of his time. He provided a wider space and various layers of secondary meanings for characters, setting, and events in the story, which resonated in many respects with the events of his contemporary time. In addition, this study unpacked the fact that savagery existed inside the human heart and manifested in a lack of guardianship and civilizational forces in human beings. This paper will be useful in exploring the novel for a better understanding of human nature.